The Effectiveness of Guided Inquiry Through Flashcard Media on Force Material to Important Critical Thinking Skills of Elementary School Students - Ani Suryani; Aan Widiyono (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Critical thinking skills are essential 21st-century competencies that students must master. However, the results of PISA 2022 show that Indonesian students scored only 383 in science, far below the OECD average of 489, indicating weak analytical and problem-solving abilities. This study was motivated by persistent challenges in developing critical thinking skills among Indonesian elementary students, as indicated by consistently low PISA scores. It investigates the effectiveness of integrating the Guided Inquiry learning model with flashcards to enhance fourth-grade students' critical thinking skills, specifically regarding the abstract topic of force in science. Employing a pre-experimental design with a one-group pretest-posttest method, the research involved 30 purposively selected students from SD Negeri 3 Kalipucangkulon. Data were collected through critical thinking skill tests and analyzed using the Paired Samples T-Test, Cohen's d for effect size, and supported by the Shapiro-Wilk normality test. The results revealed a statistically significant and substantial improvement: the mean pretest score of 51.0 (SD=15.11) increased to 77.1 (SD=5.00) in the posttest, with a mean difference of 26.1 points. Statistical analysis confirmed a highly significant difference (t(29) = -11.0, p < 0.001) and a very large effect size (Cohen's d = 2.01). These findings demonstrate that the synergistic combination of Guided Inquiry's investigative framework and the concrete, engaging nature of flashcard media is highly effective in fostering students' analytical, evaluative, and inferential skills. The study concludes that this integrated strategy offers a practical and impactful approach to creating interactive, higher-order thinking-oriented science learning in elementary schools, addressing a crucial gap in 21st-century science education. The limitations of this study, particularly the lack of a control group, highlight the necessity for subsequent research employing more rigorous designs.